The valuation effects of stock splits and stock dividends - Grinblatt, Mark S.; Masulis, Ronald W.; Titman, Sheridan (Journal of Financial Economics, 1984)
This study presents evidence which indicates that stock prices, on average, react positively to stock dividend and stock split announcements that are uncontaminated by other contemporaneous firm-specific announcements. In addition, it documents significantly positive excess returns on and around the ex-dates of stock dividends and splits. Both announcement and ex-date returns were found to be larger for stock dividends than for stock splits. While the announcement returns cannot be explained by forecasts of imminent increases in cash dividends, the paper offers several signalling based explanations for them. These are consistent with a cross-sectional analysis of the announcement period returns.